Interpretative trajectories toward understanding personhoods in prehistory - Budja, Mihael (Documenta Praehistorica, 2012)
This paper present the genesis of discussions of individual and dividual aspects of person(hood). It discuses actual interpretations of different modes of personhood: individuality and indivisibility, dividuality, partibility and fractality, and permeability in archaeology and anthropology. It focuses on the heterogeneity of past identities in European Mesolithic, Neolithic and Bronze Age contexts.
Keywords: bronasta doba; Europe; Evropa; identiteta; mezolitik; neolitik; osebnost; osebnostni razvoj; personality